Pengaruh Media Audiovisual terhadap Pengetahuan dan Keterampilan Menyikat Gigi Anak di TK An-Nahl - Najhoa Sonia Putri; Willia Novita Eka Rini; Puspita Sari; Adelina Fitri; Vinna Rahayu Ningsih (Pusat riset dan Inovasi Nasional, 2025)
Dental and oral health problems in early childhood in Indonesia are still a serious concern. This study aims to determine the effect of audiovisual media on improving the knowledge and skills of brushing teeth of early childhood in An-Nahl Kindergarten, Jambi City. The research method used a quasi-experimental design with a one group pretest-posttest design. The sample of this study was 40 children aged 4-5 years, taken using a total sampling technique. The research instruments included a knowledge questionnaire and an observation sheet for brushing teeth skills. The results showed a significant increase in knowledge scores from 3.03 to 7.33 and skills from 2.43 to 6.80 after being given an intervention in the form of audiovisual media. In conclusion, audiovisual media is effective in improving the knowledge and skills of brushing teeth of early childhood.